Environmental hydrogeochemistry and genesis of fluoride in groundwaters of Dindigul district, Tamilnadu (India) - Chidambaram, S.; Bala Krishna Prasad, M.; Manivannan, R.; Karmegam, U.; Singaraja, C.; Anandhan, P.; Prasanna, Mohan Viswanathan; Manikandan, S. (Springer, 2013)
Fluoride (F-) is an indispensable element for the human’s skeletal and dental health at prescribed levels and becomes lethal at higher levels. Spatial–temporal variability of F- and its geochemical control/association with other dissolved ions in groundwater in the Dindigul district of Tamilnadu (India) were conducted to describe the geochemical dynamics of F– in response to seasonal variability. High concentrations of fluoride (≥1.5 mg L-1) were observed in the northern region of the district. High levels of F- were observed in non-monsoon periods and low levels in monsoon, because of dilution by precipitation. Bicarbonate was well correlated with F- which explains that both ions were derived from the weathering. While F- has a very weak correlation with silica, this implies that the silicate weathering does not supply F- to the groundwater system. The F- pollution in Dindigul groundwaters is mainly driven by two factors: (1) the geogenic weathering inputs, the geology of this area mainly comprises fluoride bearing minerals (e.g. hornblende biotite gneiss and charnockite); (2) the anthropogenic inputs (agri-fertilizers and tannery waste). Further, F- in the study area is mainly attributed to geogenic sources during pre and postmonsoons and anthropogenic sources in monsoon periods.